Did this as a hw problem, got it wrong obviously. Not too sure how to solve it otherwise(adsbygoogle = window.adsbygoogle || []).push({});

1. The problem statement, all variables and given/known data

Let f be a function from A to A. Prove that for all m,n ε N, f^m*f^n = f^(m+N)

2. Relevant equations

3. The attempt at a solution

f^(m+1) f^(n+1) = f(f^m) * f(f^n)

= f(f^m * f^n) <--- this I think is what I did wrong

= f(f^(m+n)) since a^m * a^n = a^(m+n)

= f^(m+n+1)

= f^(x+1) where x = m+n

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Discrete Math: Functions with Powers

**Physics Forums | Science Articles, Homework Help, Discussion**